Understanding the Impact of Family Firms Through Social Capital Theory: A South American Perspective - Duarte Alonso, Abel; Kok, S.; O’Brien, S. (2020)
This exploratory study investigates the impact of family firms as a product of their contributions, and proposes a framework, which associates these with the adopted social capital theory. Interviews with owners of six firms operating in three different South American countries not only revealed the more familiar contributions of creating employment and instilling values, but also through business opportunities, growth, a sense of community and increasing knowledge. Aligned with various dimensions of social capital theory, several observable premises emerged, for instance, through the creation of value gained from developing links between individuals, developing local niches, or reciprocity.